MyD Shoe: Steps Forward / Roseamilda Mansor and Nurul Hayani Abd Rahman. - Mansor, Roseamilda; Abd Rahman, Nurul Hayani (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2020)
Aidora Abdul Hamid and her husband, Mairizal Misnan, started selling Crocs styled shoes and sandals at the end of 2011 under the registered business name of MyD Shoe. They began with a rented pushcart at Giant Seri Kembangan and then expanded to three other locations over the next eight years. In early 2011, Aidora sold clothes but faced challenges due to a lack of demand and low sales. She then decided to study the changes in the market. Aidora and Mairizal observed at the shopping complex for several weeks in May 2011. Their observation indicated that people go to the shopping complex to buy things that are easy to grab with reasonable affordability. After analyzing the people's purchasing attitude, the couple concluded that people love to buy things that are closely related to their lifestyle at reasonable prices. Thus, they decided to focus on her permanent job's tasks and responsibilities at a stage agency in Selangor. After a thorough discussion on the business's future and their family, Mairizal resigned from his job. He plans to focus on the business. This case study illustrates the challenges faced by entrepreneurs who dare to start a new business and the dilemmas confronting them in taking the business forward and ensuring its future growth. Throughout the years, from 2012 to 2018, this business generated positive and encouraging cash inflows. However, a change in the business environment caused by the COVID-19 pandemic in 2019, the business cash inflow has dropped by 23 percent. Thus, Aidora has to decide the future of their business. The options are 1) close down any outlet that does not show positive cash inflows or 2) open a new outlet at a new location with better business potential. This case study encourages readers to think critically in terms of strategic marketing and entrepreneur decision making.